2009
DOI: 10.1158/1078-0432.ccr-09-1013
|View full text |Cite
|
Sign up to set email alerts
|

Local Biosynthesis of Estrogen in Human Endometrial Carcinoma through Tumor-Stromal Cell Interactions

Abstract: Purpose: The metabolism and synthesis of intratumoral estrogens are thought to play a very important role in the etiology and progression of endometrial carcinoma. Aromatase is a key enzyme in the conversion of androgens to estrogens, and aromatase localization studies have reported that aromatase immunoreactivity and mRNA were detected mainly in stromal cells. However, the effect of tumor-stromal interactions on local estrogen biosynthesis in endometrial carcinomas remains largely unknown. Experimental Design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…4,25) We utilized MCF-7 cells, which produce E2 at pmol levels (i.e., 0.26 pM/10 6 cells), 26) and in the presence of exogenously added 1 nM E2, as expected, the stimulation of ERα by bisphenols was not detected in MCF-7 cells (Fig. 2).…”
Section: Discussionmentioning
confidence: 68%
“…4,25) We utilized MCF-7 cells, which produce E2 at pmol levels (i.e., 0.26 pM/10 6 cells), 26) and in the presence of exogenously added 1 nM E2, as expected, the stimulation of ERα by bisphenols was not detected in MCF-7 cells (Fig. 2).…”
Section: Discussionmentioning
confidence: 68%
“…As the plasma concentrations of A-dione in postmenopausal women are ~4-fold higher than those of T (Simpson, 2002; Keefe et al, 2014), aromatase mainly converts A-dione to E1. Currently, the data on aromatase expression in EC are controversial, with everything from high levels, to no significant differences between diseased and normal tissues, to no expression being reported (Yamamoto et al, 1993; Watanabe et al, 1995; Berstein et al, 2005; Jongen et al, 2005; Segawa et al, 2005; Lanišnik Rižner et al, 2006; Pathirage et al, 2006; Smuc and Rizner, 2009; Takahashi-Shiga et al, 2009; Lepine et al, 2010; Cornel et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…We could also clearly demonstrate that using this co-culture technique, an interaction with fibroblastic stromal cells is important in the expression of aromatase in parenchymal or carcinoma cells of lung [39] and endometrial [50] as well as breast carcinoma. These findings in co-culture system confirmed that carcinoma-stromal interactions do play pivotal and critical roles in induction of estrogen dependency through the aromatase in several types of human estrogen dependent malignancies.…”
Section: Co-culture Vs Mono-culture In Aromatase Expression and Actimentioning
confidence: 66%